(untitled) (A Social Science and Entrepreneurship Journal, 2024)
This article analyzes the entrepreneurial journey of Kofchi, a fried chicken business that managed to rise after its founder was laid off due to the COVID-19 pandemic. In facing post-layoff challenges, Kofchi managed to turn the crisis into a business opportunity through a self-taught learning approach and utilization of digital platforms for marketing. This study uses a descriptive qualitative approach to understand the dynamics of entrepreneurship, with data collected through in-depth interviews and observations at Kofchi outlets in Tasikmalaya. The results show that Kofchi’s success is driven by product innovation, competitive pricing, and social media-based marketing strategies such as TikTok and Instagram. In addition, good operational management, strict implementation of SOPs, and an integrated financial system are the keys to success in maintaining product consistency and customer satisfaction. Although faced with challenges such as fierce competition and customer complaints, Kofchi managed to overcome these obstacles through proper business strategy management. This story inspires other entrepreneurs to stay focused, innovative, and adaptable